The association between body mass index and mortality in diabetic patients with end-stage renal disease is different in hemodialysis and peritoneal dialysis - Hanri Afghahi; Salmir Nasic; Johan Svensson; Helena Rydell; Anna Wärme; Björn Peters (Renal Failure)
Background and hypothesis There are diverse results in terms of the association between body mass index (BMI) and mortality risk in patients with end-stage renal disease (ESRD). The aim was to examine if there is an association between BMI and the risk of all-cause mortality in patients with diabetes mellitus (DM) and ESRD on hemodialysis (HD) or peritoneal dialysis (PD).Methods Included were 3,235 patients (mean age 66 ± 14 years, 66% men) with DM on dialysis treatment (2,452 HD, 783 PD) that were followed for 3.9 ± 3.5 years. BMI was calculated as weight (kg)/[height (m)]2 and defined as the mean BMI value during the study period. Relationships between BMI and all-cause mortality were examined by Cox-models to estimate hazard ratios (HR) and 95% confidence intervals (CI) in univariate and multivariate analyses adjusted for demographics, laboratory findings and comorbidity. BMI between 18.5 and 25 kg/m2 was used as the reference group.Results During the study, 1,688 (53%) patients died (1,275 on HD, 413 on PD). In multivariate analyses, patients on HD with BMI ≤ 18.5 kg/m2 had an increased risk of all-cause mortality (HR1.94, CI 1.47–2.54). In contrast, mortality risk was decreased in the BMI groups of 25.1–30 kg/m2 (HR0.84, CI0.73–0.96), 30.1–35 kg/m2 (HR0.66, CI0.55–0.78), and 35.1–40 kg/m2 (HR0.65, CI0.49–0.85). In multivariate analyses, no associations between BMI and mortality risk were found in patients on PD.Conclusion An increased risk of mortality in underweight DM patients on HD was found. Overweight, class 1 and class 2 obesity were associated with better survival in HD.Key learning points The association between BMI and risk of mortality is different in patients with DM on maintenance HD or PD.What was known (maximum 50 words) The association between BMI and risk of mortality in ESRD population on dialysis treatment is very divers and different study have shown different results.This study adds (maximum 50 words) High BMI associated with better survival in patients with diabetes and HD but this finding did not observed with PD.Potential impact (on practice or understanding, maximum 50 words) The importance to examine time-varying BMI frequently as independent covariance in patients with dialysis treatment.